(untitled) (Research, Society and Development, 2021)
In various situations in the day-to-day of the endodontic clinic, the professional is faced with the need to carry out the work in more than one session. Therefore, it is imperative to select the appropriate temporary restorative material, which does not allow marginal percolation and prevents contamination of the root canal system. Microleakage consists of the passage of fluids from one place to another, and in the oral cavity, it can occur towards the inside of the tooth via the material-tooth interface, taking microorganisms, toxins and chemical substances into the root canal, which would promote the treatment failure. For this, it is necessary to maintain the aseptic chain, through chemical-mechanical preparation and, if there is a need to use a temporary restorative material to seal the endodontic access cavity, it should act as a real barrier to marginal infiltrations. Temporary restorative materials are used in Endodontics to ensure efficient sealing between treatment sessions, as well as after the end of treatment, until the tooth is definitively restored. Several researches are carried out in search of an ideal restorative material. Various materials have been the subject of research and investigation. However, it is essential to perform a temporary restoration in endodontic procedures of multiple consultations, preventing contamination of the root canal system. This article consists of a literature review that addresses the relationship between coronary microleakage and the performance of temporary restorative materials, widely used between endodontic treatment sessions.